Diabetes Nutrition Education and A Food Security Resource for American Indian and Alaska Native Adults With Type 2 Diabetes: A Pilot and Feasibility Randomized Controlled Trial - Sarah A. Stotz; Luciana Hebert; Kelli Begay; Michelle Dennison; Carmen Byker Shanks; Seth A. Berkowitz; Luohua Jiang; Jessica Lafromboise; Nicholas Begick; Barbara Cunningham; Aisa Trice; Danielle Duran; et al. (Journal of Nutrition Education and Behavior, 2026)

Food variety affects food selection and variety-seeking behaviors in an immersive virtual reality food buffet - John W. Long; Paige M. Cunningham; Kathleen L. Keller; Barbara J. Rolls; Travis D. Masterson (Appetite, 2026)

Sensory-specific satiety and the influence of variety on snack intake in school-aged children - Paige M. Cunningham; Cara T. Meehan; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2026)

High satiety: Evaluating determinants of energy compensation and intake in multiple preloading studies - Barbara J. Rolls; Liane S. Roe; Paige M. Cunningham; Kathleen L. Keller; Faris M. Zuraikat (Appetite, 2025)

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Food switching at a meal is positively associated with change in adiposity among children at high-familial risk for obesity - Nicholas V. Neuwald; Alaina L. Pearce; Paige M. Cunningham; Marissa N. Setzenfand; Lauren Koczwara; Barbara J. Rolls; Kathleen L. Keller (Appetite, 2025)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Poorer inhibitory control was related to greater food intake across meals varying in portion size: A randomized crossover trial - Paige M. Cunningham; Liane S. Roe; Alaina L. Pearce; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2024)

Reasons for meal termination, eating frequency, and typical meal context differ between persons with and without a spinal cord injury - Gary J. Farkas; Paige M. Cunningham; Alicia M. Sneij; John E. Hayes; Mark S. Nash; Arthur S. Berg; David R. Gater; Barbara J. Rolls (Appetite, 2024)

Variety and portion size combine to increase food intake at single-course and multi-course meals - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Switching between bites of food and sips of water is related to food intake across meals varying in portion size - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Fourth-Grade Cooking and Physical Activity Intervention Reveals Associations With Cooking Experience and Sex - Leslie Cunningham-Sabo; Barbara Lohse; Claudio R. Nigg; Robert J. Parody (Journal of Nutrition Education and Behavior, 2023)

Eating rate and bite size were related to food intake across meals varying in portion size: A randomized crossover trial in adults - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Anouk E.M. Hendriks-Hartensveld; Barbara J. Rolls (Appetite, 2023)

Fuel for Fun Process Evaluation Reveals Strong Implementation and Approval with Varied Parent Engagement - Leslie Cunningham-Sabo; Barbara Lohse; Jessica Clifford; Alixanna Burg; Claudio Nigg (Journal of Nutrition Education and Behavior, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate-Relevant Ocean Transport Measurements in the Atlantic and Arctic Oceans - Barbara Berx; Denis Volkov; Johanna Baehr; Molly Baringer; Peter Brandt; Kristin Burmeister; Stuart Cunningham; Marieke de Jong; Laura de Steur; Shenfu Dong; Eleanor Frajka-Williams; Gustavo Goni; et al. (Oceanography, 2021)

Measuring auditory cortical responses in Tursiops truncatus - Matt D. Schalles; Dorian S. Houser; James J. Finneran; Peter Tyack; Barbara Shinn-Cunningham; Jason Mulsow (Journal of Comparative Physiology A, 2021)
Auditory neuroscience in dolphins has largely focused on auditory brainstem responses; however, such measures reveal little about the cognitive processes dolphins employ during echolocation and acoustic communication. The few previous studies of mid- and long-latency auditory-evoked potentials (AEPs) in dolphins report different latencies, polarities, and magnitudes. These inconsistencies may be due to any number of differences in methodology, but these studies do not make it clear which methodological differences may account for the disparities. The present study evaluates how electrode placement and pre-processing methods affect mid- and long-latency AEPs in ( Tursiops truncatus ). AEPs were measured when reference electrodes were placed on the skin surface over the forehead, the external auditory meatus, or the dorsal surface anterior to the dorsal fin. Data were pre-processed with or without a digital 50-Hz low-pass filter, and the use of independent component analysis to isolate signal components related to neural processes from other signals. Results suggest that a meatus reference electrode provides the highest quality AEP signals for analyses in sensor space, whereas a dorsal reference yielded nominal improvements in component space. These results provide guidance for measuring cortical AEPs in dolphins, supporting future studies of their cognitive auditory processing.

Arctic Mediterranean exchanges: a consistent volume budget and trends in transports from two decades of observations - Svein Østerhus; Rebecca Woodgate; Héðinn Valdimarsson; Bill Turrell; Laura de Steur; Detlef Quadfasel; Steffen M. Olsen; Martin Moritz; Craig M. Lee; Karin Margretha H. Larsen; Steingrímur Jónsson; Clare Johnson; et al. (Ocean Science, 2019)
The Arctic Mediterranean (AM) is the collective name for the Arctic Ocean, the Nordic Seas, and their adjacent shelf seas. Water enters into this region through the Bering Strait (Pacific inflow) and through the passages across the Greenland–Scotland Ridge (Atlantic inflow) and is modified within the AM. The modified waters leave the AM in several flow branches which are grouped into two different categories: (1) overflow of dense water through the deep passages across the Greenland–Scotland Ridge, and (2) outflow of light water – here termed surface outflow – on both sides of Greenland. These exchanges transport heat and salt into and out of the AM and are important for conditions in the AM. They are also part of the global ocean circulation and climate system. Attempts to quantify the transports by various methods have been made for many years, but only recently the observational coverage has become sufficiently complete to allow an integrated assessment of the AM exchanges based solely on observations. In this study, we focus on the transport of water and have collected data on volume transport for as many AM-exchange branches as possible between 1993 and 2015. The total AM import (oceanic inflows plus freshwater) is found to be 9.1 Sv (sverdrup, 1 Sv =106 m3 s−1) with an estimated uncertainty of 0.7 Sv and has the amplitude of the seasonal variation close to 1 Sv and maximum import in October. Roughly one-third of the imported water leaves the AM as surface outflow with the remaining two-thirds leaving as overflow. The overflow water is mainly produced from modified Atlantic inflow and around 70 % of the total Atlantic inflow is converted into overflow, indicating a strong coupling between these two exchanges. The surface outflow is fed from the Pacific inflow and freshwater (runoff and precipitation), but is still approximately two-thirds of modified Atlantic water. For the inflow branches and the two main overflow branches (Denmark Strait and Faroe Bank Channel), systematic monitoring of volume transport has been established since the mid-1990s, and this enables us to estimate trends for the AM exchanges as a whole. At the 95 % confidence level, only the inflow of Pacific water through the Bering Strait showed a statistically significant trend, which was positive. Both the total AM inflow and the combined transport of the two main overflow branches also showed trends consistent with strengthening, but they were not statistically significant. They do suggest, however, that any significant weakening of these flows during the last two decades is unlikely and the overall message is that the AM exchanges remained remarkably stable in the period from the mid-1990s to the mid-2010s. The overflows are the densest source water for the deep limb of the North Atlantic part of the meridional overturning circulation (AMOC), and this conclusion argues that the reported weakening of the AMOC was not due to overflow weakening or reduced overturning in the AM. Although the combined data set has made it possible to establish a consistent budget for the AM exchanges, the observational coverage for some of the branches is limited, which introduces considerable uncertainty. This lack of coverage is especially extreme for the surface outflow through the Denmark Strait, the overflow across the Iceland–Faroe Ridge, and the inflow over the Scottish shelf. We recommend that more effort is put into observing these flows as well as maintaining the monitoring systems established for the other exchange branches.

Effects of fendiline on cocaine-seeking behavior in the rat - Jonathan J. Cunningham; Erin Orr; Barbara C. Lothian; Jennifer Morgen; Karen Brebner (Psychopharmacology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

3rd Annual Conference of the Leverhulme Centre for Integrative Research on Agriculture and Health (LCIRAH), Developing methods in agriculture and health research, London, 13–14 June 2013 - Jody Harris; Mieghan Bruce; Elisa Cavatorta; Laura Cornelsen; Barbara Häsler; Rosie Green; Emily H. Morgan; Sara Stevano; Helen L. Walls; Kenda Cunningham (Food Security, 2013)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Landscape effects on crop pollination services: are there general patterns? - Taylor H. Ricketts; James Regetz; Ingolf Steffan‐Dewenter; Saul A. Cunningham; Claire Kremen; Anne Bogdanski; Barbara Gemmill‐Herren; Sarah S. Greenleaf; Alexandra M. Klein; Margaret M. Mayfield; Lora A. Morandin; Alfred Ochieng’; et al. (Ecology Letters, 2008)
Pollination by bees and other animals increases the size, quality, or stability of harvests for 70% of leading global crops. Because native species pollinate many of these crops effectively, conserving habitats for wild pollinators within agricultural landscapes can help maintain pollination services. Using hierarchical Bayesian techniques, we synthesize the results of 23 studies – representing 16 crops on five continents – to estimate the general relationship between pollination services and distance from natural or semi‐natural habitats. We find strong exponential declines in both pollinator richness and native visitation rate. Visitation rate declines more steeply, dropping to half of its maximum at 0.6 km from natural habitat, compared to 1.5 km for richness. Evidence of general decline in fruit and seed set – variables that directly affect yields – is less clear. Visitation rate drops more steeply in tropical compared with temperate regions, and slightly more steeply for social compared with solitary bees. Tropical crops pollinated primarily by social bees may therefore be most susceptible to pollination failure from habitat loss. Quantifying these general relationships can help predict consequences of land use change on pollinator communities and crop productivity, and can inform landscape conservation efforts that balance the needs of native species and people.

Increased risk for developmental delay in Saethre-Chotzen syndrome is associated with TWIST deletions: an improved strategy for TWIST mutation screening - Juanliang Cai; Barbara K. Goodman; Ankita S. Patel; John B. Mulliken; Lionel Van Maldergem; George E. Hoganson; William A. Paznekas; Ziva Ben-Neriah; Ruth Sheffer; Michael L. Cunningham; Donna L. Daentl; Ethylin Wang Jabs (Human Genetics, 2003)